Assessing the mechanical behaviour of adobe masonry under uniaxial compressive strength. - Hafsa LAMOURI; Abdelaziz SEMCHA; Fouad GHOMARI (Journal of Materials and Engineering Structures, 2022)
Earth building has always existed on all continents; it constitutes an integral part of the cultural heritage of mankind. The present study is particularly interested in the valorisation of adobe masonry. To do this, a series of adobe units (three types: a, b and c) and adobe masonry wallets (A, B, and C) were prepared manually and infilled with 1cm thick earth mortar. In order to study the mechanical behaviour of the wallets in the laboratory, we study the mechanical behaviour of adobes and earth mortar then we apply the uniaxial loading method on the wallets. Also we present a new analytical formula which gives the mechanical properties of wallets derived from those of bricks and mortar that were determined before they were assembled. The experimental study shows that the compressive strength of wallets is 33% lower than that of adobes, and the deformations are similar to those of bricks, but they are 6 to 8 times smaller than those of mortar. The experimental mechanical properties of wallets were compared with those determined analytically. It give us results similar to the experimental ones with a ratio EManal/ EMexp equal to 1.2.